Tryptic peptide analysis of avian oncovirus gag and pol gene products. - Rettenmier, C W (1979)
Radiolabeled tryptic peptides of the gag and pol gene products of avian oncoviruses were examined. This analysis included Rous-associated virus 2 structural proteins and the Pr76gag and P180gag-pol proteins in Rous-associated virus 2-infected chicken embryo cells. The methionine- and cysteine-containing tryptic peptides of virion internal structural proteins were present in both Pr76gag and P180gag-pol, suggesting that there was no loss of gag gene-coding sequences during the generation of P180gag-pol. No overlap of gag and pol gene structural information was detected. Analysis of intermediates in the processing of Pr76gag and translation inhibition mapping with pactamycin yielded the following order of structural proteins within the Rous-associated virus 2 Pr76gag precursor: NH2-p19-p12-p27-p15-COOH. The gag and pol sequences missing in the endogenous gsmp120 protein of uninfected gs+ chicken cells were identified by comparison with those of Rous-associated virus 2 P180gag-pol.